Penggunaan Software Akuntansi Oleh UMKM: Kajian Empiris Extended UTAUT Model - Lukman Effendy; Zuhrotul Isnaini; Isnawati Isnawati (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
This study examines factors influencing micro, small, and medium enterprises’ (MSMEs) intention to use accounting software by adopting an extended UTAUT2 model that includes performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit. A quantitative survey of 252 MSME owners in Mataram City was analyzed using SEM-PLS with SmartPLS 4. The findings indicate that performance expectancy and hedonic motivation positively and significantly affect intention to use, while price value is also significant, highlighting the importance of perceived cost–benefit balance in adoption decisions. In contrast, effort expectancy, habit, facilitating conditions, and social influence are not significant. These results suggest that software providers should prioritize demonstrable performance benefits, enjoyable user experiences, and competitive pricing to attract MSMEs. Future research should employ larger, more representative samples and incorporate additional variables (e.g., digital literacy and prior technology experience) to develop a more comprehensive understanding of technology adoption determinants among MSMEs.